Efforts To Increase Mathematics Learning Outcomes Materials Of Summary Fractures Through The Media Of Fraction Cards For Students Of Class IV - Susanto, Dwi Ari (Social, Humanities, and Educational Studies (SHES): Conference Series, 2022)
The purpose of this research was to improve the learning outcomes of fourth grade students at SD Negeri 2 Sambi in the mathematics lesson on addition of fractions by using the learning media of fraction cards. The research used was Classroom Action Research (CAR) with stages namely pre-cycle, cycle I and cycle II. The stages of each cycle are planning, implementation, observation and reflection. Each meeting is carried out pre-test and post-test to determine the progress of students. In the pre-cycle the students who completed after carrying out the post test were only 15% with a class average value of 45. In the first cycle the students who completed after carrying out the post test were 69% with a class average value of 65. In the second cycle students who completed after carrying out the post test was 92% with an average grade of 90. These results indicate that the use of Fractional Card learning media can improve learning outcomes in Mathematics in class IV SD Negeri 2 Sambi.